2004
DOI: 10.1097/01.iop.0000103006.49679.23
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Endonasal Dacryocystorhinostomy Versus External Dacryocystorhinostomy

Abstract: The success rate of MENDCR (93.5%) compares favorably with that of standard external DCR (95.8% in this study). MENDCR relies on the creation of a large ostium and mucosal flap apposition. A larger, randomized prospective trial is needed to fully assess the efficacy of this new technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
115
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(124 citation statements)
references
References 45 publications
7
115
1
1
Order By: Relevance
“…Although there are reports of successful DCR with powered instrument [3] and laser DCR [7] but all the cases underwent non powered and non-laser DCR. The success rate of endonasal DCR has been reported to be very high and as good as external DCR [8,9]. Our success rate is as high as 96%.…”
Section: Discussionsupporting
confidence: 51%
“…Although there are reports of successful DCR with powered instrument [3] and laser DCR [7] but all the cases underwent non powered and non-laser DCR. The success rate of endonasal DCR has been reported to be very high and as good as external DCR [8,9]. Our success rate is as high as 96%.…”
Section: Discussionsupporting
confidence: 51%
“…Previously reported studies of paediatric DCR patients showed that 35-50% of cases were of unresolved congenital NLDO, with the remainder including punctal agenesis, lacrimal fistula, post-traumatic NLDO, and post-inflammatory canalicular obstruction. 10,11,14 A similar distribution was observed in our series in which 56 cases (54.8%) were of refractory primary congenital NLDO, and the others were of different etiologies. It should be emphasized that underlying pathology, approaches and outcomes of puncta/canaliculi dysgenesis, and lower lacrimal outflow system are quite different .…”
Section: Discussionsupporting
confidence: 60%
“…Radiation therapy slows or prevents the normal tissue contraction that occurs around the Jones tube, and extensive trauma or scar tissue can cause the tube to be hyper mobile for a prolonged period of time. 35 Children have a tendency for a vigorous repair process producing scar tissue, 11 which may be associated with a more mobile tube and associated migration.…”
Section: Eyementioning
confidence: 99%
“…The non-laser EES-DCR was performed mainly as described by Tsirbas et al 4,10 and Wu et al 39 A mixture of 2 ml of 2% lidocaine and epinephrine (1 : 1 00 000) was injected into the lateral nasal wall in addition to an external anterior ethmoidal nerve block and an infraorbital nerve block. Under direct visualization with a 451 4-mm endonasal endoscope (Karl Storz, Tuttlingen, Germany), the lateral nasal mucosa was incised in the area of the lacrimal sac fossa and removed.…”
Section: Surgical Technique Of Non-laser Ees-dcrmentioning
confidence: 99%
“…The success rate for EES-DCR, however, varies markedly from 54 to 96%. [1][2][3][4][5][6][7][8] Numerous modifications have been developed to promote ostial patency, ranging from various methods of producing the nasal mucosal and/or lacrimal sac flaps, 2,4,[9][10][11][12] varying the size of the bony ostium, 4,[12][13][14] lacrimal sac incision, 15 to stenting. 16,17 Nevertheless, ostial closure or obstruction still occurs, mostly due to excessive scars/synechia or granulation formation at the ostium.…”
Section: Introductionmentioning
confidence: 99%